Structure and strength characteristics of dispersion-hardened composite foils (films) based on iron and nickel - Il′insky, A.I.; Barmin, A.E.; Lyabuk, S.I. (Functional Materials, 2013)
Effects of hardening components (W, SiO, Al₂O₃, and ZrO₂) on structure and physical-mechanical characteristics of Fe and Ni composites were studied. The content of the hardening phases was up to 2 vol.%. It was shown experimentally that physical-mechanical characteristics of the prepared nano- crystalline materials were defined by the structure and inhomogeneous distribution of the hardening phase within a grain. The reasons for high thermal stability of the nano-composites were established. The factors determining the nano-composite relaxation resistibility and resources for its increasing were revealed.